Reversible mechanofluorochromic luminescence behaviors of 9, 10-distyrylanthracene- based compounds and their application in the rewritable papers technology. (June 2021) - Yu, Zian; Zhang, Yuqian; Wang, Chenxia; Du, Xuran; Lu, Hongguang; Wang, Qiusheng
Abstract: Mechanofluorochromic (MFC) materials display a photoluminescence color change in response to mechanical grinding and pressing. Development of an effective molecular design strategy to tune MFC activity is still challenging. Herein, seven 9, 10-distyrylanthracene (DSA)-based molecules are designed and synthesized as promising MFC materials. These molecules adopt a five-plane twisted spatial conformation that are composed of an anthryl ring and four phenyl rings. The inclusion of cyano groups and different substituents in this five-plane system causes some changes in the intramolecular charge transfer (ICT) and molecular conformation, which can directly induce new MFC activities. Among seven DSA derivatives, DSA-CN5 exhibits the highest MFC activity upon grinding. Based on the good sensitivity and repeatability of MFC process as well as suitable stability of the ground state, DSA-CN5 is selected to fabricate the rewritable papers and can be achieved in inkless printing technologies. Graphical abstract: Image 1 Highlights: ● Seven new DSA derivatives are designed and successfully synthesized. ● Photophysical properties of DSA derivatives can be easily adjusted. ● DSA-CN5 was selected to fabricate efficient rewritable papers and can be used in inkless printing technology. ● The printed content can be read distinctly both by the naked eyes and under UV lamp irradiation.